1999
DOI: 10.3168/jds.s0022-0302(99)75540-2
|View full text |Cite
|
Sign up to set email alerts
|

Nutritive Value of Corn Silage as Affected by Maturity and Mechanical Processing: A Contemporary Review

Abstract: Stage of maturity at harvest and mechanical processing affect the nutritive value of corn silage. The change in nutritive value of corn silage as maturity advances can be measured by animal digestion and macro in situ degradation studies among other methods. Predictive equations using climatic data, vitreousness of corn grain in corn silage, starch reactivity, gelatinization enthalpy, dry matter (DM) of corn grain in corn silage, and DM of corn silage can be used to estimate starch digestibility of corn silage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
142
5
10

Year Published

2001
2001
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(166 citation statements)
references
References 23 publications
9
142
5
10
Order By: Relevance
“…Milk production reflected DMI and was lowest for the cows fed the GT diet compared with the other diets (Table 6). A similar response has been observed in several studies (reviewed by Johnson et al, 1999) in which increases in DM content of corn silage beyond 35% resulted in reductions in DMI and milk yield.…”
Section: Methodssupporting
confidence: 86%
See 1 more Smart Citation
“…Milk production reflected DMI and was lowest for the cows fed the GT diet compared with the other diets (Table 6). A similar response has been observed in several studies (reviewed by Johnson et al, 1999) in which increases in DM content of corn silage beyond 35% resulted in reductions in DMI and milk yield.…”
Section: Methodssupporting
confidence: 86%
“…Higher DM silage with less extensive fermentation can result in reduced DMI, and lowered milk production, due to reduced nutritive value of the corn silage as discussed by Johnson et al (1999). Johnson et al (2002) duced corn silage NE L content with higher DM percentage; the breakpoint for peak milk yield or estimated silage NE L occurred at approximately 35% DM.…”
Section: Methodsmentioning
confidence: 99%
“…Information on the relationship between chemical composition and in situ rumen degradation characteristics of dry matter (DM), organic matter (OM), CP, starch and neutral detergent fiber (NDF) of maize silages in the scientific literature is scarce. Several in situ studies have been conducted on maize silages to determine the effect of individual factors such as maturity stage (Johnson et al, 1999;Di Marco et al, 2002;Jensen et al, 2005), chop length (Fernandez et al, 2004) and ensiling (González et al, 2010) of maize crop on the rumen degradation of specific nutrients like DM (Von Keyserlingk et al, 1996), OM (Arieli et al, 1998), CP (Von Keyserlingk et al, 1996;Shannak et al, 2000), starch (Fernandez et al, 2004;Hindle et al, 2005) and NDF (Varga and Hoover, 1983;Stensig et al, 1994;Jensen et al, 2005). In addition, often in these studies only a limited number (n = 1 to 12) of samples were investigated and compared with other feedstuffs.…”
Section: Introductionmentioning
confidence: 99%
“…A very warm summer and little precipitation in the second half of the year characterized the year 1999. In the studies reported by Johnson et al (1999) raw material quality deteriorated as the maturity of maize to be ensiled increased from 36 to 46%. Experimental silages showed advantageous chemical composition.…”
Section: Discussionmentioning
confidence: 99%